An analysis of preferences and practices related to the mode of delivery in Agra district of Uttar Pradesh - Verma, Arti; Singh, Shailendra; Nagargoje, Manisha M.; Mishra, S. K.; Singh, Saroj; Awasthi, Sarvesh (International Journal Of Community Medicine And Public Health, 2021)
Background: Preferences and actual practices in regard to delivery of pregnant women have wide variations. This study is an attempt to explore some of the socio-demographic factors responsible for preferences and practices in regard to mode of delivery among institutional deliveries in Agra district. Methods: This community based descriptive observational study was conducted among 300 eligible women of Agra district who were selected through multistage random sampling. Both bivariate and multivariate analysis was done and appropriate statistical tests were used. Results: The study found that out of 300 subjects; 272 had institutional deliveries among which 265 (97.43%) had a preference for vaginal delivery (VD) while only 7 (2.57%) had a preference for caesarean section (CS) but in actuality, 223 (81.99%) were delivered through vaginal mode while 49 (18.01%) had CS. On multiple logistic regression analysis, mode of delivery in previous pregnancy was found to have a significant association with the preference of a woman in regard to her mode of delivery with odds ratio of 9.88 (95% CI 1.46-66.80) and p=0.019. Conclusions: Preferences in regard to mode of delivery of a woman was only associated with her mode of delivery in previous pregnancy but her actual practice was also significantly associated with her place of delivery in addition to her mode of delivery in previous pregnancy.